Analisis Hukum Kejahatan Money Laundering Sebagai Tindak Pidana di Bidang Ekonomi - Munthe, Riswan; Pasaribu, Yusuf Hanafi; Hidayani, Sri (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This paper will examine the crime of money laundering as a crime in the economic field. The crime of money laundering is a crime that has its own characteristics from other crimes, because this type of crime is not a single crime but a double crime that has occurred. The purpose of this study will be to discuss the forms of money laundering based on the provisions of laws and regulations and the crime of money laundering is categorized as a crime in the economic field. The method in this study uses normative legal research, where normative research refers to concepts sourced from books, journals and written legislation. Based on the results of the study, it was found that money laundering based on the provisions of the legislation is an active crime and a passive crime, because the form of money laundering is carried out through financial institutions. Meanwhile, the form of money laundering crime is categorized as a crime in the economic field where this economic crime can be carried out in the form of placement, layering and integration.